Alkaline pretreatment of spent coffee grounds for oligosaccharides production by mannanase from Bacillus sp. GA2(1) - Wongsiridetchai, Chayaporn; Chiangkham, Watcharaphan; Khlaihiran, Narisara; Sawangwan, Thornthan; Wongwathanarat, Prasert; Charoenrat, Theppanya; Chantorn, Sudathip (Agriculture and Natural Resources, 2018)
Spent coffee grounds (SCGs) are solid wastes from the manufacturing of fresh coffee beverages which are globally popular. SCGs are composed of lignocellulosic materials which can be digested by lignocellulolytic enzymes and oligosaccharide is a product from the hydrolysis of cellulose and hemicellulose. However, the presence of lignin in lignocellulose leads to resistance in the activity of lignocellulolytic enzymes. Therefore, it is necessary to add a pretreatment step to increase the efficiency of the enzymes. Four factors were examined that impact on the SCGs pretreatment process: concentration of NaOH (0.5-2.5 Normality); ratio of SCGs to NaOH (1:1-1:5); temperature (50-121°C); and reaction time. Afterward, untreated SCGs and treated SCGs were digested by crude mannanase from Bacillus sp. GA2(1). The amounts of reducing sugar were analyzed using the dinitrosalicylic acid method. The results showed the optimum SCG-treated conditions were 0.5 N NaOH, 1:2 and 50°C for 6 h which produced 520 ± 0.01 mg/mL of reducing sugar. Mannobiose and mannotriose were detected when the oligosaccharide products were compared to the standard sugar solution using thin layer chromatography. Features of the surface of untreated SCGs and treated SCGs were observed using scanning electron microscopy and the surface of treated SCGs at 50°C still had a good appearance, with only some parts destroyed, and pores had formed. This feature would promote access into the SCGs and make the digestion process much more efficient while was also supported by the results from the reducing sugar analysis.